The Effect of Corporate Social Responsibility, Profitability, Activity Ratio, Solvency Ratio, and Liquidity Ratio on Corporate Value : (Case Study on Mining Companies Listed on the IDX for the 2014-2018 Period) - Mustari Mustari (Owner : Riset dan Jurnal Akuntansi, 2025)
This research aims to determine the influence of Corporate Social Responsibility, Profitability, Activity Ratios, Solvency, and Liquidity on Company Value in Mining Companies Listed on the IDX for the 2014-2018 period. The background of this research is the fluctuation and continued decline in coal prices year by year in the mining sector. This is a descriptive and explanatory study using multiple linear regression analysis. The software used for data analysis is Eviews 10. Data analysis in this study begins with a model test using the Common Effect Model, Fixed Effect Model, and Random Effect Model, followed by model selection tests such as the Chow test, Hausman test, and Durability Multiplier test. Classic assumption tests include normality, heteroskedasticity, autocorrelation, and multicollinearity tests. Subsequent steps involve multiple linear regression tests and hypothesis testing in the form of partial regression coefficient tests (t-tests) and determination coefficient tests. The population of this research consists of 210 financial reports, while the sample comprises 35 reports meeting the criteria of having Annual and Sustainability Reports. The data used is secondary data obtained through documentation and literature study methods. The findings indicate that CSR does not influence Firm Value (Tobin'Q), Profitability (EPS) does not affect Firm Value (Tobin'Q), Activity Ratio (TATO) influences Firm Value (Tobin'Q), Solvency (DAR) influences Firm Value (Tobin'Q), and Liquidity (CR) influences Firm Value (Tobin'Q) with a value of 0.0249. From the coefficient of determination (R2), it is concluded that Corporate Social Responsibility, Profitability, Activity Ratios, Solvency, and Liquidity have a simultaneous effect.